Biomechanical responses of elite swimmers to staleness and recovery - Hooper, S.; MacKinnon, L. T.; Wilson, B. (1995)
Tethered swimming forces (TSF), average distance achieved per stroke (D/S) during a submaximal effort swim, and time and D/S for a maximal effort swim were measured to determine changes occurring with staleness and recovery. Fourteen nationally ranked male and female swimmers were studied five times (i.e. early-, mid-, and late-season, during tapering, and after competition). ANOVA and Newman-Keuls post-hoc tests were used to assess changes during the season. Three swimmers were classified as stale and showed a deterioration (0.7%) in maximal performance time from early- to late-season which was significantly different (P < 0.05) from the improvement (3.1%) demonstrated by the non-stale swimmers. Daily self-ratings of fatigue, kept by the swimmers in log books during the season, were significantly higher (P < 0.001) for the stale compared with the non-stale swimmers. No significant differences were established between the stale and non-stale swimmers in TSF or D/S during the season or in the response to tapering. A significant improvement (P < 0.05) in TSF was observed from before to after tapering. It was concluded that TSF and D/S may not change significantly with staleness and that the recovery period of tapering prior to competition allows swimmers to generate greater forces in the water. Aust J Sci Med Sport 1995 Mar;27(1):9-13